2018
DOI: 10.1177/1203475418808761
|View full text |Cite
|
Sign up to set email alerts
|

Dermatology-Related Uses of Medical Cannabis Promoted by Dispensaries in Canada, Europe, and the United States

Abstract: There is a growing interest in the use of medical cannabis for a variety of dermatologic conditions. Despite the lack of evidence to validate the effectiveness and safety of marijuana, it is approved to treat a variety of dermatologic conditions in the United States. Furthermore, medical cannabis dispensaries have been making unsubstantiated claims about medical cannabis. It is important for dermatologists to know about the purported use of medical cannabis to help patients navigate this new treatment option, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 16 publications
0
17
0
2
Order By: Relevance
“…Spironolactone is emerging as a potential alternative to oral antibiotics. 2,3 However, little is known about long-term outcomes with spironolactone for those who have an initial positive response and how it compares with other alternatives.…”
Section: Real-world Drug Usage Survival Of Spironolactone Versus Oralmentioning
confidence: 99%
See 1 more Smart Citation
“…Spironolactone is emerging as a potential alternative to oral antibiotics. 2,3 However, little is known about long-term outcomes with spironolactone for those who have an initial positive response and how it compares with other alternatives.…”
Section: Real-world Drug Usage Survival Of Spironolactone Versus Oralmentioning
confidence: 99%
“…1 While therapeutic applications are under study, over-the-counter topical cannabinoids have been promoted for use in skin conditions on the basis of limited evidence. 2 The risk of allergic contact dermatitis posed by these products is unclear. We sought to characterize the formulations and allergenic potential of topical cannabinoids.…”
mentioning
confidence: 99%
“…1 In vitro susceptibility was tested by using the disk diffusion method as previously reported. Phylotype was determined according to the method recently developed by Barnard et al 2 SLST was performed on all isolates as described by Scholz et al 3 Macrolide and tetracycline resistance were investigated as previously described. Wilcoxon and Fisher exact tests were used to compare both groups.…”
Section: Real-world Drug Usage Survival Of Spironolactone Versus Oralmentioning
confidence: 99%
“…A paper indicated that suggested and advertised dermatological use of medical cannabis by dispensaries across USA, Canada and Europe are largely unsubstantiated. 34 This may leave parents and patients in difficult with regards to accurate information gathering. Research performed with adults with all subtypes of EB have shown pharmaceutical grade CBD-based medicines can improve pain scores, reduce pruritus and reduce overall analgesic drug intake.…”
Section: Novel Therapiesmentioning
confidence: 99%